2015
DOI: 10.1002/ange.201505192
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Amidation of Nitroalkanes with Amine Nucleophiles using Molecular Oxygen and Iodine

Abstract: The formation of amides and peptides often necessitates powerfuly et mild reagent systems.T he reagents used, however,a re often expensive and highly elaborate.N ew atom-economical and practical methods that achieve such goals are highly desirable.I deally,t he methods should start with substrates that are readily available in both chiral and non-chiral forms and utilize cheap reagents that are compatible with awide variety of functional groups,steric encumberance, and epimerizable stereocenters.Adirect oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…This iodine-catalyzed diazo activation originated from an accidental discovery 17 20 . It has been recently reported that aryl diazonium salts (ArN 2 + ) are effective oxidants in promoting gold(I) oxidation to gold(III) 21 23 .…”
Section: Resultsmentioning
confidence: 99%
“…This iodine-catalyzed diazo activation originated from an accidental discovery 17 20 . It has been recently reported that aryl diazonium salts (ArN 2 + ) are effective oxidants in promoting gold(I) oxidation to gold(III) 21 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally,arecentr eport by Hayashi on the possible activation of N-iodosuccinimide with amine groups (Scheme 9) [28] promptedt he investigation on related reactivity in the present system.W hile allylamine turned out to be incompatible with iodine(I)r eagent 3c,r elated acetamides promoted the iodooxygenation of 4-fluorostyrene 4g to the corresponding product 6t in aw ay that is comparable to activation with 2-chlorobenzoic acid. Although due to instability in solution,n os tructural data has become available yet, an activation of the iodine(I)b y acetamide similart ot he case of Hayashi is proposed to be involved in this case.…”
Section: Resultsmentioning
confidence: 99%
“…Popular community detection algorithms used for SNA include Factorised Asymptotic Bayesian (FAB) inference with Belief Propagation, an algorithm which strengths lies in having no parameters, effecting consistent results over sparse and dense graph even as its extended version is known to lack consistency based on the usage of the Belief Propagation [14]. Another popular algorithm used for detecting community via SNA is the modularity optimisation and maximum likelihood equivalence algorithm.…”
Section: Isomorphic Graph Algorithmmentioning
confidence: 99%